The Effect of CEO Overconfidence and Leverage on Dividend Policy. - I Gede Dandi Aryadika; Anak Agung Gde Putu Widanaputra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Dividend policy is an important aspect of corporate financial management, especially for public companies that are obligated to provide returns to shareholders. Dividend policy reflects the company’s strategic decision to distribute profits or retain them for reinvestment. The purpose of this study is to determine and obtain empirical evidence regarding the influence of CEO overconfidence and leverage on dividend policy. The population in this study consists of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, totaling 58 companies. The sample was selected using a non-probability sampling method with a purposive sampling technique, resulting in a sample of 174 observations. There were 27 outlier data points, so the final number of observations used in this study was 147. In this study, the analysis technique used was the multiple linear regression analysis technique with the help of SPSS software. The results show that CEO overconfidence has a positive and significant effect on dividend policy, while leverage has no effect on dividend policy.